Faktor Utama Keberhasilan Proyek Bangunan Elektronik di Kab. Enrekang - Ahmad Mahatir H (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
This study aims to identify the success factors of building projects. The method used was data collection through questionnaires filled out by 30 respondents, including project owners, survey consultants, contractors, supervisors, and foremen. The results of validity and reliability tests showed that the variables of cost (X1), time (X2), quality (X3), and safety (K3L) were valid as they had an r-value greater than the r-table value of 0.361. The data analysis results indicated that the dominant factors influencing the success of building projects in the hypothesis testing were the t-values: Cost (X1) at 3.514, Time (X2) at 3.64, Quality (X3) at 4.66, and Safety (K3L) at 3.342. It can be concluded that the variables of Cost and Safety (K3L) are more significant or dominant compared to Quality and Time.